Evaluasi Pelaksanaan Tindakan Penagihan Pajak Terhadap Wajib Pajak Pailit di KPP XYZ - Tosan Yanuar Rachmadi; Yulianti Abbas (Owner : Riset dan Jurnal Akuntansi, 2025)
Tax collection action is a tool to enforce tax payers to pay their tax debts,but tax collection action such as seizure of assets and auctions can not be executed by the Directorate General of Taxes in a bankrupt case because it is prohibited by Bankruptcy Law. To ensure successful tax debt collection from bankruptcy tax payers, states provide preemptive rights in tax collection actions. However, the issuance of the Constitutional Court’s Decision No. 67/PUU-XI/2013, which places the Directorate General of Taxes in third place in the settlement of bankruptcy assets after labor rights and separatist creditor bills, will increase the possibility of uncollectible tax debts. Because in a bankrupt case, preemptive rights can not be applied, tax debts must contend with other bills to be paid by the curator. This study aims to evaluate tax collection actions based on successful tax debt management in order to minimize uncollectible tax debts. This study uses the case study method, which is conducted at XYZ Tax Office. Data collection through document analysis, literature review, and interviews. The results of this study show that the Directorate General of Taxes has implemented Constitutional Court Decision Number 67/PUU-XI/2013, and XYZ Tax Office has proposed to write off some of the bankruptcy tax payer debts that have expired in accordance with regulations.